Inula Viscosa Extract Inhibits Growth of Colorectal Cancer Cells in vitro and in vivo Through Induction of Apoptosis - Bar-Shalom, Rinat; Bergman, Margalit; Grossman, Shlomo; Azzam, Naiel; Sharvit, Lital; Fares, Fuad (Frontiers in Oncology, 2019)
Colorectal cancer (CRC) is the second most common cancer in females and the third in males worldwide. Conventional therapy of CRC is limited by severe side effects and by development of resistance. Therefore, additional therapies are needed in order to combat the problem of selectivity and drug resistance in CRC patients. Inula viscosa (IV) is a well known medicinal perennial herb in traditional medicine. It is used for therapeutic purposes, such as; topical anti-inflamatic, diuretic, haemostatic, antiseptic, antiphlogistic and in the treatment of diabetes. Several studies attempted to reveal the anti-cancer activity of different extracts prepared by different organic solvents from different parts of the IV plant. The aims of the present study were to examine the potential beneficial effects of IV leaves aqueous extract on growth of colon cancer cells in vitro and in vivo. The results indicated that exposure of colorectal cancer cells to IV extract, significantly reduced cell viability in a dose and time dependent manner. Moreover, treatment of cells with 300 µg/ml of IV extract induced apoptosis, as it was detected by Annexin V/ FITC/PI, TUNEL assay and activation of caspases. In vivo studies revealed that treatment with 150 or 300 mg/kg IV extract inhibited tumor growth in mice transplanted with MC38 cells. Tumors' weight and volume were significantly (P˂0.001) reduced when compared to untreated-control group. Staining of paraffin section from the tumors revealed that IV treatment inhibited cell proliferation and induced apoptosis. Additionally, no side effects such as; weight loss, behavior changes, ruffled fur or changes in kidney and liver functions were observed. These results may indicate that the active doses of IV extract are not toxic. Further studies are needed in order to identify the structure of the active compounds. Results from this research may contribute to the development of new and efficient strategies for treatment of human colon cancer.